Pemikiran Epistemologi Filsafat Pancasila dalam Konteks Pengembangan Ilmu Pengetahuan - Dipo Piswatama; Depi Yohana Manurung; limra G.M Nababan; Santiana Siboro; Ramsul Yandi Nababan (Departement of Mathematics Education, 2024)
Epistemological thinking of the Pancasila philosophy in the context of the development of science means whether elementary school students in Indonesia understand the theoretical values ​​of Pancasila in a book. The aim of this research is to find out whether sixth grade elementary school students know the basic values ​​of Pancasila. This type of research is qualitative. Qualitative research methods focus on interviewing other people in external and complex environments. (Moleong, 1999; Creswell, 2002, Lindloft, 1995), states that qualitative research methods are more inductive. This means that the research step that must be prioritized is data based on facts, symptoms, phenomena, reality which is the theme, then processed, processed, so that at the end of the research it can become a proposition, model or even theory. The solution to this problem is to have qualified teachers, provide socialization in the school, and practice the basic values ​​of Pancasila, and not just verbally in Pancasila and citizenship education books.